Metaphors in Melengkan of the Gayo Language: An Ecolingistic Perspective - Ananda, Rizki; Marisa, Vera; Hutasuhut, Nurul Inayah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
Melengkan, a form of traditional oral expression performed during wedding ceremonies in the Gayo community of Aceh, Indonesia, is rich in metaphorical language. This study analyses the metaphors found in Melengkan from an Ecolinguistics perspective. Using a qualitative approach, the research examines how these metaphors reflect cultural values and ecological awareness. This research identifies and analyzes three dominant metaphorical domains found in Gayo marriage melengkan: Nature-Based Metaphors, Social Relationship Metaphors, and Moral-Ethical Metaphors. Nature-based metaphors illustrate ecological awareness, portraying elements like trees, rivers, clouds, and wind as symbols of harmony, resilience, and balance in marital life. Social metaphors highlight the communal aspect of marriage, reinforcing values such as kinship, consensus, and collective responsibility. Moral and ethical metaphors emphasize adat (customary law), integrity, and spiritual obligations within the institution of marriage. The findings reveal that melengkan is not only a medium of cultural expression but also a reflection of the Gayo people's eco-centric worldview, where language serves to sustain both environmental and social harmony. This study contributes to the broader understanding of how traditional oral literature embodies ecological values and reinforces sustainable cultural practices through metaphorical language.The findings reveal that Melengkan embodies expressions that symbolize social harmony and the interconnection between humans and nature. This suggests that local oral traditions play a crucial role in preserving both cultural identity and ecological knowledge.